Storing water: a new integrated approach for resilient development - Yu, W.; Rex, William; McCartney, Matthew P.; Uhlenbrook, Stefan; Gnechten, Rachel von; Priscoli, J. D. (2021)
This paper outlines a new and integrated water storage agenda for resilient development in a world increasingly characterised by water stress and climate uncertainty and variability.|Storing water has long been a cornerstone of socio-economic development, particularly for societies exposed to large climatic variability. Nature has always supplied the bulk of water storage on earth, but built storage has increased significantly, particularly over the twentieth century. Today, numerous countries suffer from water storage gaps and increasingly variable precipitation, threatening sustainable development and even societal stability. There is a growing need to develop more storage types and manage existing storage better. At the same time, the policy, engineering, and scientific communities may not fully recognise the extent of these storage gaps and how best to manage them. There are large and uncertain costs and benefits of different types of storage, and developing storage can be risky and controversial. Although there is consensus that built and natural storage are fundamentally complementary, there is still no pragmatic agenda to guide future integrated water storage development.|This paper argues that water storage should be recognised as a service rather than only a facility. More than volumes of water stored behind a dam or in a watershed, what ultimately matters is the ability to provide different services at a particular time and place with a given level of assurance. Integrated storage systems should be developed and managed to deliver a targeted service standard. This will reduce the costs of new storage development and make the benefits more sustainable.|As this paper demonstrates, there are numerous data gaps pertaining to water storage, as well as a need for greater clarity on some key concepts. This paper does not introduce new data or research but rather provides a review of some of the current knowledge and issues around water storage, and outlines a new, integrated and constructive water storage agenda for the decades to come.